Large-Scale Age-Dependent Skewed Sex Ratio in a Sexually Dimorphic Avian Scavenger - Lambertucci, Sergio Agustin (2012)
Age-dependent skewed sex ratios have been observed in bird populations, with adult males generally outnumbering females. This trend is mainly driven by higher female mortality, sometimes associated with anthropogenic factors. Despite the large amount of work on bird sex ratios, research examining the spatial stability of adult sex ratios is extremely scarce. The Andean condor (Vultur gryphus) is the only bird of prey with strong sexual dimorphism favouring males (males are 30% heavier than females). By examining data from most of its South-American range, we show that while the juvenile sex ratio is balanced, or even female-skewed, the sex ratio becomes increasing male-skewed with age, with adult males outnumbering females by >20%, and, in some cases by four times more. This result is consistent across regions and independent of the nature of field data. Reasons for this are unknown but it can be hypothesized that the progressive disappearance of females may be associated with mortality caused by anthropogenic factors. This idea is supported by the asymmetric habitat use by the two sexes, with females scavenging in more humanized areas. Whatever the cause, male-skewed adult sex ratios imply that populations of this endangered scavenger face higher risks of extinction than previously believed.